Quality of life and sleep impairment in chronic cocaine dependents Qualidade de vida e comprometimento do sono em dependentes crônicos de cocaína - Adriana Lima; Sueli Rossini; Rubens Reimão (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To evaluate quality of life (QL) and sleep quality impairment of cocaine chronic dependents in use of cocaine. METHOD: 40 patients, chronic cocaine dependents were evaluated (37 M; 3 F), with mean age of 28.92 years, along with 40 controls paired for gender and age. The following instruments were used: a) the semi-structured clinical interview; b) the Brazil Economic Classification; c) the Pittsburgh Sleep Quality Index; d) World Heath Organization Quality of Life-BREF (WHOQOL-BREF). RESULTS: The cocaine dependents showed QL impairment, with deficits in the physical, psychological and social relations domains. Impaired sleep quality was also observed in the cocaine dependents. However, the QL impairment was not directly due to sleep deficit. CONCLUSION: Chronic cocaine dependents showed impairment in QL and sleep impairment. However, for the cocaine dependent group, sleep impairment was not regarded as compromising QL probably because cocaine, rather than sleep, was the main factor negatively influencing QL. OBJETIVO: Avaliar a qualidade de vida (QV) em dependentes de cocaína na fase de uso de droga e comprometimento da qualidade do sono. MÉTODO: Foram avaliados 40 pacientes dependentes de cocaína (37 M; 3 F), com média de idade de 29,92 anos; e 40 controles, equiparando-se as variáveis de gênero e idade e utilizando-se os seguintes instrumentos: a) Entrevista clínica semi-dirigida; b) Classificação Econômica Brasil; c) Índice de Qualidade do Sono de Pittsburgh; d) World Health Organization Quality of Life-BREF (WHOQOL-Breve). RESULTADOS: Os dependentes de cocaína apresentaram prejuízo na QV, com alterações nos domínios físico, psicológico e também das relações sociais. No grupo estudo não houve associação entre QV e qualidade do sono, ou seja, para os sujeitos desta amostra, a qualidade do sono não afetou a QV. CONCLUSÃO: No grupo estudo a QV foi considerada prejudicada, mas não devida de forma primordial ao comprometimento da qualidade do sono. Nestes pacientes a cocaína é provavelmente o fator primordial negativo sobre a QV e não o comprometimento do sono.